2022
DOI: 10.1371/journal.pone.0268213
|View full text |Cite
|
Sign up to set email alerts
|

Challenging ecogeographical rules: Phenotypic variation in the Mountain Treeshrew (Tupaia montana) along tropical elevational gradients

Abstract: Bergmann’s and Allen’s rules were defined to describe macroecological patterns across latitudinal gradients. Bergmann observed a positive association between body size and latitude for endothermic species while Allen described shorter appendages as latitude increases. Almost two centuries later, there is still ongoing discussion about these patterns. Temperature, the common variable in these two rules, varies predictably across both latitude and elevation. Although these rules have been assessed extensively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
1
2
1
Order By: Relevance
“…Additionally, Allen’s rule fitted for ear length in both rodent species. Thus, our results agree with several related studies, suggesting that evidence does not allow us to support a general extension of these ecogeographic rules in small mammals along elevational gradients [ 19 , 20 , 21 , 47 , 52 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Additionally, Allen’s rule fitted for ear length in both rodent species. Thus, our results agree with several related studies, suggesting that evidence does not allow us to support a general extension of these ecogeographic rules in small mammals along elevational gradients [ 19 , 20 , 21 , 47 , 52 ].…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, various aspects of body appendages can exhibit diverse trends, even within the same species. For example, in the mountain treeshrew Tupaia montana, tail length conformed to this rule, ear length remained unchanged, and the hindfoot displayed a general opposite pattern across elevational gradients [ 21 ]. If changes in ear size contribute to thermal adaptation in cold, high montane regions (an extension of Allen’s rule), we would expect to observe a reduction in ear length with increasing elevation—this was observed in our two model species, as well as in the Chinese pygmy dormouse T. cinereus [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have found that Bergmann’s rule or the island rule are inverted or inapplicable in other treeshrew species 14 , 36 , 37 , ours is the first to demonstrate an interaction between these two rules in this group of mammals, and one of the very few to show this in any mammalian species 11 , 12 , 38 . Mainland individuals of T. belangeri display a clear reversal of Bergmann’s rule, whereas island individuals increase in size with latitude as expected (Figs.…”
Section: Discussioncontrasting
confidence: 65%